Islamic Religious Education for Children with Social Emotional Barriers - Khoshimov, Maksud (Jurnal Asesmen Dan Intervensi Anak Berkebutuhan Khusus, 2024)
Some experts in the United Kingdom mention that the homeless are children who have emotional disorders. In this research discussed how a person's self-identity inhibits the development of his emotions. There are three aspects that need to be explored related to one that is inherent in a person and his environment. These three aspects are ego, an identity that shows its existence in the outside world. and social identity in the solidarity of a person in line with the ideals of a group. As for the research related to the homeless how a homeless person or adolescent can carry out his duties as a person and social, of course this is related to the identity and social of homeless adolescents. The child's self-identity is formed through the development of stable and good emotions and social. Of course, the environment also greatly affects the process. The development of children's emotions and social in forming self-identity together also forms a good understanding of children's lives. Therefore, the need for religious education to form an understanding of life that will be realized in the behaviour of children. The results of this study showed that there is a change in behaviour and emotions in children with disabilities with the granting of religious guidance to children with disabilities.